2015
DOI: 10.3892/ol.2015.3634
|View full text |Cite
|
Sign up to set email alerts
|

Guillain Barré Syndrome in a multiple myeloma patient after the first course of bortezomib therapy: A case report

Abstract: Abstract. Bortezomib is approved for treating relapsed multiple myeloma (MM) and mantle cell lymphoma, and clinical evidence has shown complete clinical responses in MM patients. Peripheral neuropathy is one of the most common adverse effects of bortezomib. However, rare evidence has shown that bortezomib is associated with Guillain-Barré syndrome (GBS). In the present study, a case of GBS is reported in an MM patient finishing the first course of bortezomib therapy. Based on a bone marrow cell examination rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…33 , 39 , 40 However, the appearance of neurotoxic side effects like BiPNP has restrained research on further modes of action of proteasome inhibitors. 15–17 As reported above, this toxic polyneuropathy occurs mainly when BTZ is administered frequently (1.3 mg/m² given s.c. on Days 1, 4, 8 and 11, and every 21 days thereafter for three or four cycles) in multiple myeloma patients. Our experimental setup shows for the first time that one cycle of low dose BTZ application can ameliorate clinical, electrophysiological and histological signs of neuritis.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…33 , 39 , 40 However, the appearance of neurotoxic side effects like BiPNP has restrained research on further modes of action of proteasome inhibitors. 15–17 As reported above, this toxic polyneuropathy occurs mainly when BTZ is administered frequently (1.3 mg/m² given s.c. on Days 1, 4, 8 and 11, and every 21 days thereafter for three or four cycles) in multiple myeloma patients. Our experimental setup shows for the first time that one cycle of low dose BTZ application can ameliorate clinical, electrophysiological and histological signs of neuritis.…”
Section: Discussionmentioning
confidence: 78%
“…This effect is of main clinical importance as immediate withdrawal of the drug after development of a toxic sensory neuropathy can reverse neuropathic symptoms in multiple myeloma patients with BiPNP. 15–17 Interestingly, the high concentration of BTZ did not exert any immunomodulatory effects in the flow cytometry analyses or qPCR on immune cell populations. NFKB pathway was not modulated.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The difference may be due to species and/ or dosages of BTZ used in patients and animals [27,28]. Nonetheless, this prior animal study further showed that anti-TNF-α alleviated a decrease of density of myelinated fibers.…”
Section: Discussionmentioning
confidence: 95%
“…A prior human study showed no evidence of demyelination in patient treated with BTZ [27]; whereas a study using mice demonstrated a loss of myelinated fibers of peripheral sensory nerves after BTZ administration [28]. The difference may be due to species and/ or dosages of BTZ used in patients and animals [27,28].…”
Section: Discussionmentioning
confidence: 99%